Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/s00122-002-1131-x
|View full text |Cite
|
Sign up to set email alerts
|

An EREBP/AP2-type protein in Triticum aestivum was a DRE-binding transcription factor induced by cold, dehydration and ABA stress

Abstract: We characterize one transcription factor of DRE-binding proteins (TaDREB1) that was isolated from a drought-induced cDNA library of wheat (Triticum aestivum L.). TaDREB1 contains one conserved EREBP/AP2 domain, and shows similarity with Arabidopsis thaliana DREB family members in both overall amino-acid sequences and the secondary structure arrangement within the DNA-binding motifs. In yeast one-hybrid system, TaDREB1, can specially activate the genes fused with the promoter containing three tandemly repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
177
1
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(190 citation statements)
references
References 30 publications
(33 reference statements)
2
177
1
4
Order By: Relevance
“…Constitutive overexpression of some stress-responsive transcription factor genes, such as DREBs, controlled by the CaMV 35S promoter frequently caused unwanted phenotypes, such as reduced plant growth, that finally caused significant reduction of potential yield (37). However, transgenic plants (T 0 ) or families (T 1 and T 2 ) of SNAC1 showed no obvious difference from the WT plants in all of the traits investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutive overexpression of some stress-responsive transcription factor genes, such as DREBs, controlled by the CaMV 35S promoter frequently caused unwanted phenotypes, such as reduced plant growth, that finally caused significant reduction of potential yield (37). However, transgenic plants (T 0 ) or families (T 1 and T 2 ) of SNAC1 showed no obvious difference from the WT plants in all of the traits investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis and rice, the subtype 1 genes DREB2A and OsDREB2B have the highest stress inducibility among the DREB2 genes and have been shown to play significant roles in DREmediated stress responses in both plant species (Sakuma et al, 2002(Sakuma et al, , 2006a(Sakuma et al, , 2006bMatsukura et al, 2010). In addition, many stress-inducible DREB2-type transcription factors that have been identified to date belong to subtype 1 (Shen et al, 2003;Xue and Loveridge, 2004;Egawa et al, 2006;Agarwal et al, 2007;Qin et al, 2007;Matsukura et al, 2010). Therefore, we focused on the eight subtype 1 genes: GmDREB2A;1, GmDREB2A;2, GmDREB2B;1, GmDREB2B;2, GmDREB2C;1, GmDREB2C;2, GmDREB2D;1, and GmDREB2D;2.…”
Section: Identification and Classification Of Dreb2-type Transcriptiomentioning
confidence: 99%
“…The inducibility in response to stress conditions is a common feature among DREB2-type transcription factors of various plants, and the promoter structure including these cis-elements is conserved among many eudicot species Mizoi et al, 2012). In Poaceae (grass family), posttranscriptional control by alternative splicing works as a key regulatory mechanism of DREB2-type transcription factors, although this alternative splicing mechanism is not found in other plant families (Shen et al, 2003;Qin et al, 2007;Matsukura et al, 2010). In Arabidopsis, the accumulation of DREB2A mRNA is not sufficient for the induction of downstream genes, and posttranslational regulation is important in activating DREB2A (Liu et al, 1998;Sakuma et al, 2006a).…”
mentioning
confidence: 99%
“…Earlier studies demonstrated that the expression of the CBF genes in Arabidopsis resulted in an increased tolerance to freezing, salt and drought stresses (Liu et al 1998;Jaglo-Ottesen et al 1998;Kasuga et al 1999;Gilmour et al 2000). The cDNAs encoding CBF transcription factors have been identified and cloned from various plant species including Arabidopsis, rice, wheat, canola, soybean (Liu et al 1998;Dubouzet et al 2003;Shen et al 2003;Li et al 2005). In the present investigation, we have cloned and characterized the first member of CBF gene Fig.…”
Section: Discussionmentioning
confidence: 84%
“…DREB2-like genes, belong to the A-2 subgroup, are mainly involved in regulation of genes responsive to osmotic stress (Sakuma et al 2002;Nakashima and Yamaguchi-Shinozaki 2006). Arabidopsis homologs of DREB1/CBF genes have been isolated and characterised in evolutionarily diverse plants with different levels of adaptation to cold stress such as, common wheat (Triticum aestivum L.), rice (Oryza sativa L.), rye (Secale cereale L.), maize (Zea mays L.), canola (Brassica napus), etc., and overexpression of DREB1/CBF genes in transgenic plants increases tolerance to drought, high salt, and freezing stresses (Dubouzet et al 2003;Shen et al 2003;Qin et al 2004;Zhang et al 2004a;Hong and Kim 2005;Benedict et al 2006;Zhao et al 2006;Chinnusamy et al 2010). So, CBF genes may be useful for improving the stress tolerance of crops (Yamaguchi- .…”
Section: Introductionmentioning
confidence: 99%